EM Duality and Quasinormal Modes from Higher Derivatives with Homogeneous Disorder. (21st August 2019) - Fu, Guoyang; Wu, Jian-Pin
Abstract : We study the electromagnetic (EM) duality from6 derivative theory with homogeneous disorder. We find that, with the change of the sign of the coupling parameterγ 1 of the6 derivative theory, the particle-vortex duality with homogeneous disorder holds better than that without homogeneous disorder. The properties of quasinormal modes (QNMs) of this system are also explored. When the homogeneous disorder is introduced, some modes emerge at the imaginary frequency axis for negativeγ 1 but not for positiveγ 1 . In particular, with an increase in the magnitude ofα ^, new branch cuts emerge for positiveγ 1 . These emerging modes violate the duality related to the change of the sign ofγ 1 . With the increase ofα ^, this duality is getting violated more.